KOMUNIKASI HUBUNGAN ROMANTIS DALAM FENOMENA TA'ARUF DI INDONESIA - Agustin Meliana Wiganda, (2022)
This study aims to find out in-depth about the romantic relationship communication contained in ta'aruf relationships by using Devito's interpersonal communication theory, social exchange theory, and expectations violation theory as supporting theories. The subjects in this study were individuals who were married through the ta'aruf process and individuals who had undergone the ta'aruf process but chose to end the process and did not proceed to marriage. The method used is qualitative with a phenomenological approach. The sources of data in this study are primary data sources and secondary data. The researcher uses four stages of data analysis in Heidegger's phenomenological research, namely: 1) horizontalization, 2) textural description, 3) structural description, and 4) description of the meaning of the phenomenon. The final result of this research found that each individual has a different value of rewards and costs in establishing a ta'aruf relationship. Rewards are elements in the relationship in the form of positive values, while costs are elements that are identical with negative values. The valuation is formed from their relationship experiences in the past, the life stories of those closest to them, and the character of themselves, so that the valuation of the value of rewards and costs for each individual is different depending on the life journey they have gone through. In this research, the informants considered the attitudes and characteristics of the ta'aruf partner to be the most important reward values considered for the continuation of the relationship, then added to other factors, namely religion, stability, physical, occupation, income, regional origin, association, visionary individual, education, and good communication skills. According to the informants, the most important costs value to consider in the ta'aruf relationship also comes from the attitudes and characteristics of the ta'aruf partner followed by other factors, namely bad habits, inappropriate principles, appearance, poor morals, bad friendship environment, and bad time management. At the comparison level (CL), informants who married through the ta'aruf process said they were satisfied with the relationship they had, while four out of five informants who chose to end the ta'aruf process were not satisfied with their ta'aruf relationship, one other admitted that her ta'aruf relationship had met the expected standard of the relationship. At the comparison level for alternatives (CLalt), two out of ten informants have other alternative candidates that they can choose during the ta'aruf process, but they still choose to continue the ta'aruf relationship with their ta'aruf partner at the time. This indicate that the ta'aruf relationship of the informants is running stably